2011
DOI: 10.1097/ccm.0b013e31821cb40e
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial inducible nitric oxide synthase causes bacterial translocation by impairment of enterocytic tight junctions via intracellular signals of Rho-associated kinase and protein kinase C zeta*

Abstract: Epithelial inducible nitric oxide synthase activates two distinct signals, protein kinase C ζ and Rho-associated kinase, to disrupt tight junctions leading to bacterial influx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 51 publications
1
46
0
1
Order By: Relevance
“…Bacterial endocytosis by epithelial cells was observed after 6 h of obstruction, whereas TJ damage was seen only after 24 h. 15,29,57 The TJ damage in gut tissues after 24 h of obstruction was evidenced by occludin cleavage, ZO-1 destruction, and increased tissue conductance and macromolecular permeability. 15,29,57 Interestingly, continuous epithelial lining on villus surface with no sign of cell death was found at both time points, ruling out loss of cell viability as a cause of bacterial transcellular passage. Normal crypt/villus ratio was observed after 6 h in comparison to villus blunting without crypt hyperplasia after 24 h, suggesting cell sloughing on villus tip may partly contribute to TJ damage at the later time point.…”
Section: Terminal Web Contraction and Brush Border Fanningmentioning
confidence: 99%
See 4 more Smart Citations
“…Bacterial endocytosis by epithelial cells was observed after 6 h of obstruction, whereas TJ damage was seen only after 24 h. 15,29,57 The TJ damage in gut tissues after 24 h of obstruction was evidenced by occludin cleavage, ZO-1 destruction, and increased tissue conductance and macromolecular permeability. 15,29,57 Interestingly, continuous epithelial lining on villus surface with no sign of cell death was found at both time points, ruling out loss of cell viability as a cause of bacterial transcellular passage. Normal crypt/villus ratio was observed after 6 h in comparison to villus blunting without crypt hyperplasia after 24 h, suggesting cell sloughing on villus tip may partly contribute to TJ damage at the later time point.…”
Section: Terminal Web Contraction and Brush Border Fanningmentioning
confidence: 99%
“…[73][74][75] Although the innate immune response as an early warning system is aiming for bacterial elimination, excessive inflammatory and oxidative/nitrosative stress may act as double-edged swords and result in bystander damage to intestinal barrier integrity. Death-dependent TJ disruption or cell death-independent signaling for TJ impairment have been documented in intestinal epithelial cells following exposure to ROS and NO, [27][28][29] as well as IFNg, TNFa, and IL-1b. 21,22,26 We and others demonstrated that bacterial endocytosis by epithelial cells preceded TJ damage under inflammatory stress in a doseand time-dependent manner.…”
Section: Intracellular Immune Signalsmentioning
confidence: 99%
See 3 more Smart Citations